1997
DOI: 10.1152/ajpendo.1997.273.1.e37
|View full text |Cite
|
Sign up to set email alerts
|

Cholate inhibits high-fat diet-induced hyperglycemia and obesity with acyl-CoA synthetase mRNA decrease

Abstract: The effects of sodium cholate on high-fat diet-induced hyperglycemia and obesity were investigated. Insulin resistance was estimated by measuring 2-deoxyglucose uptake in epitrochlearis muscles incubated in vitro. Addition of 0.5% cholate to high-safflower oil diet completely prevented high fat-induced hyperglycemia and obesity in C57BL/6J mice with a slight decrease of energy intake but with no inhibition of fat absorption. Furthermore, the addition of cholate decreased blood insulin levels and prevented high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 30 publications
5
31
1
4
Order By: Relevance
“…Bile acids strongly affect metabolism and energy expenditure in mice (11,12,20). From studies in rats, it is known that supplementing low fat, casein-based diets with rather high doses of glycine and/or taurine affects bile acid metabolism (29,70,71).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bile acids strongly affect metabolism and energy expenditure in mice (11,12,20). From studies in rats, it is known that supplementing low fat, casein-based diets with rather high doses of glycine and/or taurine affects bile acid metabolism (29,70,71).…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional Regulation of Endogenous BA Metabolism Modulates High Fat Diet-induced Hyperglycemia-Oral BA treatment reduces hyperglycemia in mice (12), possibly through reduced hepatic glucose output by repression of the Pck1 gene expression (13,14). In addition, PPAR␤/␦ activation reduces hepatic glucose output and improves peripheral glucose disposal (67).…”
Section: Nutritional Regulation Of Endogenous Ba Metabolism Modulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…When overexpressed in hepatocytes, transcriptional regulator liver X receptor ␣, which directly senses diverse lipid metabolites as ligands (38), elevates mouse serum lipid profiles on a normal diet but improves high blood lipid profiles and protects from atherosclerosis in mice on a Western diet (39). It should also be noted that bile acids reduce high-fat diet-induced hyperglycemia and triglyceride accumulation in liver (36). FGFR4 Ϫ/Ϫ mice display increased bile acid levels (20).…”
Section: Discussionmentioning
confidence: 99%
“…BAs are known regulators of energy homeostasis and glucose metabolism that have been reported to inhibit dietinduced obesity and prevent the development of insulin resistance (Ikemoto et al 1997, Kobayashi et al 2007, Keitel et al 2008b. Watanabe et al (2006) have shown that administration of BAs to mice increases energy expenditure in BAT, preventing obesity and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%